Heavy Alpine snowfall in January 2019 connected to atmospheric blocking. (16th June 2021) - Yessimbet, Kamilya; Ossó, Albert; Kaltenberger, Rainer; Magnusson, Linus; Steiner, Andrea K.
Abstract : In January 2019, an episode of extreme, record‐breaking snowfall hit the northern part of the Alps. The event was linked to persistent North Atlantic blocking, which transported moisture from the North Atlantic towards the Alps. At the same time, the polar vortex was displaced over the North Atlantic, split, and a major sudden stratospheric warming occurred. We discuss the possible role of blocking in the polar vortex split and the onset of the sudden stratospheric warming as well as its implications in predicting the snowfall event.